2022
DOI: 10.1177/11297298211067630
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ experiences of cannulation of arteriovenous access for haemodialysis: A qualitative systematic review

Abstract: Introduction: Cannulation is an essential part of haemodialysis with arteriovenous access. Patients’ experiences of cannulation for haemodialysis are problematic but poorly understood. This review aims to synthesise findings related to patients’ experiences of cannulation for haemodialysis from qualitative studies, providing a fuller description of this phenomenon. Methods: Eligibility criteria defined the inclusion of studies with a population of patients with end-stage kidney disease on haemodialysis. The ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 52 publications
1
5
0
1
Order By: Relevance
“…The included studies also reported that patients weigh multiple factors when deciding whether to undergo procedures to create AVFs� Patients were more likely to undergo procedures to create AVFs if a provider they trusted recommended them� However, patients often weighed the nature of past experiences with vascular access more heavily than health care providers' recommendations� Furthermore, both patients and their health care providers considered surgical procedures to create AVFs to be invasive� Patients' fears of being cut or experiencing pain or complications from these procedures could hinder their desire to engage in them� Patients also considered the anticipated outcomes of these procedures when deciding whether to undergo them� Concerns about an AVF not maturing or being easily maintained and worries about anticipated needlerelated pain could prevent patients from wanting AVFs� Additional concerns hindering patients' engagement in procedures to create AVFs included those regarding the perceived risk of bleeding, infiltrations, and aneurysms, and the anticipated impact an AVF would have on their physical appearance� The relative risk of infection between AVFs and CVLs was of lesser concern to patients� These findings corroborate those detailed in the extant literature. 15,18,38 Considering these concerns, decisionmakers would benefit from considering research investigating whether:…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%
“…The included studies also reported that patients weigh multiple factors when deciding whether to undergo procedures to create AVFs� Patients were more likely to undergo procedures to create AVFs if a provider they trusted recommended them� However, patients often weighed the nature of past experiences with vascular access more heavily than health care providers' recommendations� Furthermore, both patients and their health care providers considered surgical procedures to create AVFs to be invasive� Patients' fears of being cut or experiencing pain or complications from these procedures could hinder their desire to engage in them� Patients also considered the anticipated outcomes of these procedures when deciding whether to undergo them� Concerns about an AVF not maturing or being easily maintained and worries about anticipated needlerelated pain could prevent patients from wanting AVFs� Additional concerns hindering patients' engagement in procedures to create AVFs included those regarding the perceived risk of bleeding, infiltrations, and aneurysms, and the anticipated impact an AVF would have on their physical appearance� The relative risk of infection between AVFs and CVLs was of lesser concern to patients� These findings corroborate those detailed in the extant literature. 15,18,38 Considering these concerns, decisionmakers would benefit from considering research investigating whether:…”
Section: Conclusion and Implications For Decision-or Policy-makingmentioning
confidence: 99%
“…Insertion of needles into a large blood vessel is a necessary but invasive and unpleasant experience for many patients receiving hemodialysis through an arteriovenous fistula. 1 Most must undergo the insertion and removal of at least 6 large-bore needles per week, totaling more than 300 needling procedures per year. Needle-related distress influences kidney replacement therapy and vascular access choices, including preferences for and reluctance to remove dialysis catheters.…”
mentioning
confidence: 99%
“…Needle-related distress influences kidney replacement therapy and vascular access choices, including preferences for and reluctance to remove dialysis catheters. 1 , 2 , 3 , 4 , 5 Needle-related distress is likely underreported by patients, who accept it as the price for remaining alive with dialysis. 1 , 6 Needle fear has been reported by 25% to 47% of adults receiving dialysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 A equipe de enfermagem, em especial o enfermeiro, são os profissionais que possuem maior contato e vivência com o paciente hemodialítico, reconhecendo suas necessidades de saúde e no tratamento da doença. São também responsáveis por promover ações de educação em saúde junto ao paciente, as quais envolve o cuidado do acesso vascular.…”
unclassified